Sample preparation method and device for XRD (X-Ray Diffraction) test of microcell phase components

By covering and etching the cover on the measured surface of the sample to be tested in the XRD test, exposing the measured area, the problem of the change of the spot projection area with the angle and insufficient equipment for the micro-area accessories in the XRD micro-area test is solved, and the problem of the spot projection area changes with the angle and the insufficient equipment for the micro-area accessories in the XRD micro-area test is achieved. High precision detection of micron-level areas to be tested.

CN119470506APending Publication Date: 2025-02-18XIAMEN TUNGSTEN CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411634640.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing XRD micro-zone tests have the problem that the spot projection area changes with the angle, most diffractometers are not equipped with micro-zone accessories, and the micro-zone diffraction cannot be used for fine structural analysis using point focal spots.

Method used

By covering the selected covering on the surface of the sample to be tested, and only the area to be tested is exposed after etching the cover at the area to be tested, the phase of the area to be tested is tested using XRD to test the micron-level area to be tested. Element.

Benefits of technology

The detection of the micron-level area to be tested is not affected by the X-ray diffractometer measurement method and hardware, and the problem of the change of the spot projection area with angle and insufficient equipment for micro-area accessories is solved, and fine structural analysis can be carried out.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119470506A_ABST
    Figure CN119470506A_ABST
Patent Text Reader

Abstract

The invention discloses a sample preparation method for XRD (X-Ray Diffraction) test of microcell phase components, and belongs to the technical field of XRD phase component detection. A surface to be detected of a sample to be detected is covered with a selected covering, and then after the covering at a region to be detected of the sample to be detected is etched, only the region to be detected of the sample to be detected is exposed. Therefore, when the X-ray diffractometer is adopted to test the phase composition of the to-be-tested area, the to-be-tested surface outside the to-be-tested area has no diffraction peak or is not completely overlapped with the diffraction peak of the to-be-tested area, so that the diffraction peak spectrum of the micron-sized to-be-tested area can be obtained. According to the method disclosed by the invention, the XRD detection of the phase components of the micron-sized to-be-detected region is not limited by a measurement mode or an instrument hardware condition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of phase component detection, and in particular to a sample preparation method and device for XRD testing of micro-region phase components. Background Art

[0002] As research in the field of materials engineering continues to deepen, researchers are eager to quickly and accurately obtain relevant information about samples made by different processes, such as element composition and distribution, surface morphology, phase and crystal structure, etc., so as to verify the accuracy of process theory and guide and achieve refined production. In addition to macro performance testing, micro-level testing can help researchers better understand these research objects.

[0003] At present, there are many testing methods for micro-area composition and morphology analysis, such as scanning electron microscopy, electron probe, etc.; however, the restrictions on micro-area phase analysis are more stringent. For example, electron backscatter diffraction, transmission electron microscopy and other testing methods are limited by the surface roughness of the sample, the resolution rate affected by conductivity, etc., and have higher requirements for sample preparation. Although the most commonly used X-ray diffractometer for phase analysis can theoretically achieve micron-level area testing with the help of special micro-area accessories, it has many limitations in practical applications. For example, ① the area of ​​the spot changes with the angle during the test, and the projection area of ​​the low-angle spot on the sample is often larger than 1.5 times the diameter of the collimator tube; ② the diameter of the matching collimator tube has a limited range of variation, and it cannot be applied to narrow or irregular test areas; ③ if the spot is too small, it is easy to make the diffraction intensity insufficient, and replacing a high-power instrument may not have a micro-area accessory; ④ in order to increase the diffraction intensity, micro-area diffraction often uses a point focus spot, which reduces the peak shape and diffraction angle resolution, and the test results cannot be applied to fine structure analysis. Therefore, how to achieve phase composition measurement in micrometer-scale areas without changing the XRD measurement method and the hardware conditions of the measuring instrument is an urgent problem to be solved. Summary of the invention

[0004] The embodiment of the present application provides a sample preparation method and device for XRD testing of micro-region phase composition. It can solve the many limitations of XRD micro-region testing in the prior art. The technical solution is as follows:

[0005] On the one hand, a sample preparation method for XRD testing micro-region phase composition is provided, the method comprising:

[0006] Selecting a test surface of the sample to be tested, and determining a test area on the test surface;

[0007] Determine a covering, fix the covering on the surface to be tested and cover the area to be tested, the physical phase of the covering has no diffraction peak in the XRD spectrum, or the diffraction peak of the physical phase of the covering does not completely overlap with the diffraction peak of the physical phase of the area to be tested;

[0008] The covering in the area to be tested is removed to expose the area to be tested.

[0009] Optionally, determining the covering includes:

[0010] If the diffraction peak of the physical phase in the area to be measured is known, the covering is a metal foil that does not completely overlap with the diffraction peak of the physical phase in the area to be measured or a transparent melt that has no diffraction peak after curing;

[0011] If the diffraction peak of the physical phase in the region to be measured is unknown, the covering material is a transparent melt having no diffraction peak after curing.

[0012] Optionally, the melting point of the covering is below 450° C., the transparent melt is a paraffin-based melt, and the paraffin-based melt contains amorphous powder.

[0013] Optionally, the method further includes:

[0014] A marker is arranged between the cover and the area to be tested, and the area to be tested is marked with the marker to indicate the position of the area to be tested.

[0015] Optionally, when the covering material is transparent melt adhesive, the marking material is oily ink, and the marking material is distributed around the outer boundary of the area to be tested or covers the area to be tested.

[0016] Optionally, when the covering material is a metal foil, the marker is an adhesive, and the marker is distributed around the outer boundary of the area to be tested or covers the area to be tested. After the metal foil covers the surface to be tested, the metal foil is pressed to make the metal foil at the edge of the area to be tested bulge.

[0017] Optionally, the thickness of the metal foil is in a range of 20 micrometers to 40 micrometers, and the thickness of the transparent melt adhesive after curing is in a range of 200 micrometers to 500 micrometers.

[0018] On the other hand, a sample preparation device for XRD testing of micro-region phase composition is provided, the device comprising:

[0019] A mounting component, wherein the mounting component is used to fix the covering on the test surface of the sample to be tested and cover the test area on the test surface, and the physical phase of the covering has no diffraction peak in the XRD spectrum, or does not completely overlap with the diffraction peak of the physical phase in the test area;

[0020] An etching component is used to etch the covering in the area to be tested to expose the area to be tested.

[0021] Optionally, the etching component includes: a sample carrier, a lifting bracket, a magnifying glass, an illuminator, a clamp and a heating device, the sample carrier is used to carry the sample to be tested, the lifting bracket is movably connected to the sample carrier, the magnifying glass and the illuminator are both movably mounted on the lifting bracket; the heating device has a replaceable heating head, and the heating head is mounted on the clamp;

[0022] The clamp is used to fix the heating head and can adjust the angle. The heating device is used to etch the covering of the area to be tested through the heating head.

[0023] Optionally, the heating head comprises at least one of a tungsten steel needle with a diameter of 0.1 μm-500 μm, an alloy tip with a diameter of 0.1 μm-500 μm, and an alloy flat head with a diameter of 1 mm-5 mm.

[0024] Optionally, the device further comprises: a marker installation component, wherein the marker installation component is configured to carry a marker and mark the marker to the outer boundary of the area to be tested.

[0025] The beneficial effects brought by the technical solution provided by the embodiment of the present application include at least:

[0026] A sample preparation method for testing alloy micro-region phase composition, by covering the test surface of the sample to be tested with a selected covering material, and then etching the covering material at the test area of ​​the sample to be tested to expose only the micron-level test area of ​​the sample to be tested. In this way, when the phase composition of the micron-level test area is tested by XRD, the test surface outside the test area has no diffraction peak or does not completely overlap with the diffraction peak of the test area, and the diffraction peak spectrum of the micron-level test area can be obtained. The method of the present invention makes the detection of the micron-level test area not affected by the measurement method and hardware of the X-ray diffractometer, and can solve the current problems such as the projection area of ​​the light spot emitted by the X-ray light source on the sample changes with the diffraction angle, most diffractometers are not equipped with micro-region accessories, and the micro-region diffraction using point focus spots cannot perform fine structural analysis on the test results. In addition, the sample to be tested formed by the above-mentioned sample preparation method for testing micro-region phase composition, combined with the conventional XRD measurement method, can realize the testing of the narrow or irregular micron-level test area in the sample to be tested. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0028] Figure 1 It is a flow chart of a sample preparation method for XRD testing micro-region phase composition provided in an embodiment of the present application;

[0029] Figure 2 It is a flow chart of another sample preparation method for XRD testing micro-region phase composition provided in an embodiment of the present application;

[0030] Figure 3 This is a flow chart of another sample preparation method for XRD testing of micro-region phase composition provided in an embodiment of the present application;

[0031] Figure 4 This is a flow chart of another sample preparation method for XRD testing of micro-region phase composition provided in an embodiment of the present application;

[0032] Figure 5 It is a system block diagram of a sample preparation device for XRD testing of micro-region phase composition provided in an embodiment of the present application;

[0033] Figure 6 It is a structural schematic diagram of a sample preparation device provided in an embodiment of the present application;

[0034] Figure 7 This is a metallographic observation photograph of a cross section of a tungsten wire provided in an embodiment of the present application;

[0035] Figure 8 yes Figure 7 A local magnified metallographic observation photograph at point A;

[0036] Fig. 9 It is a schematic diagram after covering the target area with a covering;

[0037] Fig.10 is a schematic diagram after etching the covering material at the area to be tested;

[0038] Fig.11 It is the XRD spectrum formed after the phase composition test of the tested area;

[0039] Fig.12 This is a metallographic observation photograph of a high-temperature sintered silicon-molybdenum solder provided in an embodiment of the present application;

[0040] Fig.13 This is a further magnified metallographic observation photo of the high-temperature sintered silicon-molybdenum solder;

[0041] Fig.14 It is a schematic diagram after covering the target area with a covering;

[0042] Fig.15 is a schematic diagram after etching the covering material at the area to be tested;

[0043] Fig.16 It is the XRD spectrum obtained after the phase composition test of the tested area;

[0044] Fig.17 This is a scanning electron microscope photograph of the coating cross section direction of a CVD coated blade provided in an embodiment of the present application;

[0045] Fig.18 This is a further reduced SEM photo of the coating cross section of the CVD coated insert;

[0046] Fig.19 It is a schematic diagram after covering the target area with a covering;

[0047] Fig. 20 is a schematic diagram after etching the covering at the test area E;

[0048] Fig.21 is the XRD comparison pattern of the matrix WC before and after covering with the covering;

[0049] Fig. 22 It is the XRD spectrum obtained after the phase composition test of the tested area.

[0050] The above drawings have shown clear embodiments of the present application, which will be described in more detail later. These drawings and text descriptions are not intended to limit the scope of the present application in any way, but to illustrate the concept of the present application to those skilled in the art by referring to the embodiments. DETAILED DESCRIPTION

[0051] In order to make the objectives, technical solutions and advantages of the present application clearer, the implementation methods of the present application will be further described in detail below with reference to the accompanying drawings.

[0052] X-ray diffraction (XRD) is an effective means of phase composition testing. At present, the micro-area (the micro-area of ​​the present invention refers to the micron-level test area, specifically the test area less than 500μm) of the sample is tested by using a micro-area accessory collimator to control the size of the diffraction spot. The minimum tube diameter is 0.05 mm, reaching the theoretical micron-level range. However, during the XRD micro-area test, at least one of the following problems still exists: (1) During the test, the projection area of ​​the spot on the sample changes with the diffraction angle. The projection area of ​​the low-angle spot is often larger than 1.5 times the diameter of the collimator; (2) The diameter of the matching collimator changes discontinuously. In actual use, the narrow or irregular test area can only select the minimum diameter; the analysis area may be limited to the maximum diameter. For example, in the local semi-quantitative analysis, it is hoped that 2.5mm 2(3) Although the test results of the left and right areas are theoretically possible, the diffraction intensity obtained when the tube diameter is less than 0.5 mm is very low, and ordinary fluorescent display boards cannot even observe the signal to adjust the spot position; (4) The diffractometer of high-power target materials may not have the corresponding matching collimator, and micro-area testing cannot be performed; (5) In order to increase the diffraction intensity, micro-area diffraction often uses a point focus (the power of the point focus is larger than that of the line focus), which reduces the angular resolution and the test results cannot be applied to fine structure analysis (for example, half-width, lattice constant, microscopic strain, etc.).

[0053] Please refer to Figure 1 , Figure 1 The flowchart of a sample preparation method for XRD testing of micro-region phase composition provided in an embodiment of the present application. The sample preparation method for testing micro-region phase composition of alloy may include:

[0054] Step 101: Select a test surface of a sample to be tested, and determine a test area on the test surface.

[0055] Wherein, for example, the surface to be tested of the sample to be tested can be a clean and flat alloy sintered surface or a polished surface obtained by flat grinding and polishing. Wherein, the area to be tested of the sample to be tested is the area where the micro-region phase composition test is required to be performed using XRD.

[0056] Step 102, determine the covering, which can be fixed on the test surface of the sample to be tested and covers the test area. The physical phase of the covering has no diffraction peak in the XRD spectrum, or the diffraction slit of the physical phase of the covering does not completely overlap with the diffraction peak of the physical phase of the test area in the sample to be tested.

[0057] Among them, the diffraction peak of the physical phase of the covering does not completely overlap with the diffraction peak of the physical phase of the area to be tested in the sample to be tested, that is, the diffraction peak of the physical phase of the covering and the diffraction peak of the physical phase of the area to be tested in the sample to be tested do not have an overlapping area or only have a partial overlapping area.

[0058] Step 103: removing the covering in the area to be tested of the sample to be tested to expose the area to be tested of the sample to be tested.

[0059] After the test area in the test sample is exposed, the phase composition of the test area can be accurately tested by using an X-ray diffractometer. For example, the phase composition of the test area in the alloy sample can be tested by using a line focus spot with a diffractometer without a collimator or a point focus spot with a diffractometer with a collimator.

[0060] In an embodiment of the present application, a selected covering is covered on the surface to be tested of the sample to be tested, and then the covering at the area to be tested of the sample to be tested is removed to expose only the area to be tested of the sample to be tested. In this way, when the phase components of the area to be tested are subjected to XRD testing, the surface to be tested outside the area to be tested has no diffraction peaks or does not completely overlap with the diffraction peaks of the area to be tested, and a diffraction peak spectrum of the micron-level area to be tested can be obtained. The method of the present invention allows the detection of the micron-level area to be tested to be unaffected by the measurement method and hardware of the X-ray diffractometer, and can solve the current problems such as the projection area of ​​the light spot emitted by the X-ray light source on the sample changes with the diffraction angle, most diffractometers are not equipped with micro-area accessories, and the micro-area diffraction uses a point focus spot and cannot perform fine structural analysis on the test results. In addition, the sample to be tested formed by the above-mentioned sample preparation method for testing the micro-area phase components, combined with the conventional XRD measurement method, can realize the testing of the narrow or irregularly shaped micron-level area to be tested in the sample to be tested.

[0061] In summary, the embodiment of the present application provides a method for preparing samples for testing the phase composition of alloy micro-regions, by covering the surface to be tested with a selected covering material, and then etching the covering material at the area to be tested of the sample to be tested to expose only the area to be tested of the sample to be tested. In this way, when the phase composition of the area to be tested is tested using an X-ray diffractometer, the surface to be tested outside the area to be tested has no diffraction peak or does not completely overlap with the diffraction peak of the area to be tested, and the diffraction peak spectrum of the micron-level area to be tested can be obtained. The method of the present invention allows the detection of the micron-level area to be tested to be unaffected by the measurement method and hardware of the X-ray diffractometer, and can solve the current problems such as the projection area of ​​the light spot emitted by the X-ray light source on the sample changes with the diffraction angle, most diffractometers are not equipped with micro-region accessories, and micro-region diffraction uses a point focus spot and cannot perform fine structural analysis on the test results. In addition, the sample to be tested formed by the above-mentioned sample preparation method for testing the micro-region phase composition, combined with the conventional XRD measurement method, can realize the testing of the narrow or irregularly shaped micron-level area to be tested in the sample to be tested.

[0062] Optional, please refer to Figure 2 , Figure 2 This is a flow chart of another sample preparation method for XRD testing of micro-region phase composition provided in an embodiment of the present application. The sample preparation method may include:

[0063] Step 201: Select a test surface of a sample to be tested, and determine a test area on the test surface.

[0064] Step 202: If the diffraction peak of the phase in the area to be tested in the sample to be tested is known, a metal foil that does not completely overlap with the diffraction peak of the phase in the area to be tested in the sample to be tested, or a cured transparent melt without a diffraction peak can be selected as a covering. For example, the thickness of the metal foil can be 20 microns to 40 microns.

[0065] The diffraction peak of the phase in the test area of ​​the known sample can be obtained through advance testing. If the diffraction peak of the phase in the test area of ​​the known sample is unknown and the sample preparation efficiency needs to be improved, the following step 203 can be performed.

[0066] For example, if the distribution of Co (cobalt) phase in different areas of the cemented carbide surface is tested, a metal foil such as commercially available tin foil can be selected as a covering. When transparent melt is selected as a covering, the transparent melt has no diffraction peak under X-ray irradiation after curing. In addition, the transparent melt has a low melting point, high density and hardness, and does not chemically react with the sample to be tested.

[0067] Step 203: If the diffraction peak of the physical phase of the test area in the test sample is unknown, a transparent melt having no diffraction peak after curing can be selected as the covering material.

[0068] When transparent melt is selected as the covering material, the cured transparent melt has no diffraction peak under X-ray irradiation. In addition, the transparent melt has a low melting point, high density and hardness, and does not chemically react with the sample to be tested.

[0069] It should be noted that the transparent melt is first heated to form a molten transparent melt, and the molten transparent melt is applied to the test surface of the sample to be tested, and the transparent melt layer is pressed flat with a flat-head electric soldering iron or other tool to solidify to form a covering.

[0070] The thickness of the cured transparent melt layer may range from 200 μm to 500 μm. In order to further ensure the thickness of the cured transparent melt layer, a thickness measuring device may be used to measure the thickness of the transparent melt layer. For example, a micrometer or a vernier caliper is first used to measure the thickness of a metal sample not coated with the transparent melt, and then a micrometer or a vernier caliper is used to measure the overall thickness of the metal sample coated with the transparent melt and the transparent melt, and then the thickness of the metal sample not coated with the transparent melt is deducted from the overall thickness of the metal sample coated with the transparent melt and the transparent melt to obtain the thickness of the transparent melt.

[0071] Step 204: Etch the covering material in the area to be tested of the sample to be tested to expose the area to be tested of the sample to be tested.

[0072] If a metal foil is used as a covering, the metal foil in the area to be tested of the sample to be tested needs to be etched to expose the area to be tested of the sample to be tested; if a transparent melt without a diffraction peak is used as a covering, the transparent melt in the area to be tested of the sample to be tested needs to be etched to expose the area to be tested of the sample to be tested. It should be noted that the area of ​​the area to be tested exposed after etching the metal foil or transparent melt in the area to be tested of the sample to be tested may be smaller than the actual area of ​​the area to be tested.

[0073] In the examples of this application, please refer to Figure 3 , Figure 3 This is a flow chart of another sample preparation method for XRD testing of micro-region phase composition provided in an embodiment of the present application. The sample preparation method may include:

[0074] Step 301: Select a test surface of a sample to be tested, and determine a test area on the test surface.

[0075] Step 302 : adding amorphous powder into the molten transparent melt, and coating the molten transparent melt mixed with the amorphous powder onto the test surface of the test sample for solidification.

[0076] The transparent melt in a molten state may be a paraffin melt, and the amorphous powder may be used to reduce the diffraction peak intensity of the physical phase to prevent the diffraction peak of the physical phase in the non-test area from affecting the diffraction peak of the physical phase in the test area. For example, the transparent melt can usually reduce the diffraction peak of the physical phase of the metal with strong diffraction ability to less than one-fifth, and after the amorphous powder is mixed in the transparent melt, the diffraction peak of the physical phase of the metal with strong diffraction ability can be reduced to near zero.

[0077] Step 303: Etch the covering material in the area to be tested of the sample to be tested to expose the area to be tested of the sample to be tested.

[0078] Here, the transparent melt mixed with amorphous powder in the test area of ​​the sample to be tested needs to be etched to expose the test area of ​​the sample to be tested.

[0079] For example, the amorphous powder may be an iron-based amorphous powder. If metals such as tungsten and molybdenum exist in the non-test area, the use of the iron-based amorphous powder can reduce the diffraction peak of the metal phases such as tungsten and molybdenum to zero.

[0080] In the examples of this application, please refer to Figure 4 , Figure 4 This is a flow chart of another method for preparing samples for XRD testing of micro-region phase components provided in an embodiment of the present application. The sample preparation method may include:

[0081] Step 401: Select a test surface of the sample to be tested, and determine a test area on the test surface.

[0082] Step 402: Mark the area to be tested of the sample to be tested with a marker to indicate the position of the area to be tested of the sample to be tested.

[0083] Among them, a marker is used to mark the test area of ​​the sample to be tested, so that the operator can quickly and accurately determine the position of the test area of ​​the sample to be tested, and provide instructions for the subsequent etching of the covering in the test area.

[0084] In the present application, if transparent melt is used as the covering, the marker may be an oily ink, and the marker may be distributed around the outer boundary of the test area of ​​the test sample or cover the test area. In this way, the position of the marker can be seen from the transparent melt, which facilitates the subsequent etching of the covering in the test area of ​​the test sample.

[0085] In the present application, if a metal foil is used as a covering, the marker may be an adhesive, and the marker may be distributed around the outer boundary of the area to be tested of the sample to be tested or cover the area to be tested. After the metal foil covers the surface to be tested of the sample to be tested, the metal foil is pressed so that the portion of the metal foil located at the edge of the area to be tested of the sample to be tested is raised. In this way, since the portion of the metal foil that contacts the adhesive may protrude from other portions of the metal foil, the covering distributed in the area to be tested of the sample to be tested may be determined, which facilitates the subsequent etching of the covering in the area to be tested of the sample to be tested. For example, the marker may be a melt adhesive or a double-sided adhesive.

[0086] Step 403, determine the covering, which can be fixed on the sample to be tested and covers the area to be tested of the sample to be tested, the physical phase of the covering has no diffraction peak in the XRD spectrum, or the diffraction peak of the physical phase of the covering does not completely overlap with the diffraction peak of the physical phase of the area to be tested of the sample to be tested.

[0087] Step 404: Etch the covering material in the area to be tested of the sample to be tested to expose the area to be tested of the sample to be tested.

[0088] Based on the same technical concept, the present application also provides a sample preparation device for XRD testing of micro-region phase components, which can be used to perform a sample preparation method for XRD testing of micro-region phase components. Figure 5 , Figure 5 The system block diagram of a sample preparation device for XRD testing of micro-region phase components provided by an embodiment of the present application can include: a mounting component 200 and an etching component 300.

[0089] The mounting component 200 in the sample preparation device for XRD testing of micro-region phase composition can be used to fix the covering on the test surface of the sample to be tested and cover the test area on the sample preparation surface of the sample to be tested. The physical phase of the covering has no diffraction peak in the XRD spectrum, or does not completely overlap with the diffraction peak of the physical phase in the test area of ​​the sample to be tested.

[0090] The etching component 300 in the alloy micro-region phase composition test sample preparation device can be used to etch the covering in the test area of ​​the sample to be tested to expose the test area of ​​the sample to be tested.

[0091] In summary, the embodiment of the present application provides a sample preparation device for XRD testing of micro-area phase components, through which the sample preparation component in the device can obtain the sample preparation surface of the sample to be tested, and the installation component can fix the selected covering to the surface to be tested of the sample to be tested and cover the area to be tested of the sample to be tested. In this way, by covering the selected covering on the surface to be tested of the sample to be tested, and then etching the covering at the area to be tested of the sample to be tested by the etching component, only the area to be tested of the sample to be tested is exposed. In this way, when the phase components of the area to be tested are tested, the surface to be tested outside the area to be tested has no diffraction peak or does not completely overlap with the diffraction peak of the area to be tested, and the diffraction peak spectrum of the micron-level area to be tested can be obtained. The sample preparation method performed by the device makes the detection of the micron-level area to be tested not affected by the measurement method and hardware of the X-ray diffractometer, and can solve the current problems such as the projection area of ​​the light spot emitted by the X-ray light source on the sample changes with the diffraction angle, most diffractometers are not equipped with micro-area accessories, and the micro-area diffraction uses a point focus spot and cannot perform fine structural analysis on the test results. In addition, the sample to be tested formed by the above-mentioned sample preparation method for testing micro-region phase composition, combined with the conventional XRD measurement method, can be used to test the narrow or irregularly shaped micron-level test area in the sample to be tested.

[0092] Optional, please refer to Figure 6 , Figure 6 300 in the sample preparation device for XRD testing of micro-region phase composition may include: a sample stage 301, a lifting bracket 302, a magnifying glass 303, an illuminator (not shown in the figure), a clamp 304 and a heating device 305. The sample stage 301 can be used to carry the sample to be tested, the lifting bracket 302 can be movably connected to the sample stage 301, and the magnifying glass 303 and the illuminator can be movably mounted on the lifting bracket 302. The heating device 305 can have a replaceable heating head 305a, and the heating head 305a in the heating device 305 can be mounted on the clamp 304.

[0093] The holder 304 can be used to fix the heating head 305a in the heating device 305 and can adjust the angle. The heating device 305 can be used to etch the covering in the test area of ​​the test sample through the heating head 305a.

[0094] For example, Figure 6As shown, the clamp 304 may include: a tilt angle adjustment component 304a and a rotating support frame 304b that are interconnected, the heating head 305a in the heating device 305 is installed on the rotating support frame, the rotating support frame 304b can drive the heating head 305a in the heating device 305 to tilt within a certain angle range and rotate within a horizontal plane, and the tilt angle adjustment component 304a can drive the rotating support frame 304b and the heating head 305a to fine-tune the tilt angle as a whole.

[0095] In the present application, the heating head 305a in the heating device may include at least one of a tungsten steel needle with a diameter of 0.1 μm-500 μm, an alloy tip with a diameter of 0.1 μm-500 μm, and an alloy flat head with a diameter of 1 mm-5 mm.

[0096] For example, the heating device 305 may include: a temperature regulating device and a heating head 305a, the heating head 305a may be electrically connected to the temperature regulating device, and the temperature regulating device may be used to regulate the temperature of the heating head 305a to adapt to different usage scenarios.

[0097] In an embodiment of the present application, the alloy micro-region phase composition testing sample preparation device may also include: a marker mounting component (not shown in the figure), which can be configured to: carry a marker and mark the marker to the outer boundary of the test area in the sample to be tested or cover the test area.

[0098] For example, when the marker is oily ink, the marker mounting component can be a marker pen or a needle-like object. When the marker is an adhesive, the marker mounting component can be tweezers or a sheet-like object.

[0099] The present application embodiment uses the following three cases to illustrate the results of XRD measurement of the samples to be tested formed by the sample preparation method for XRD testing micro-region phase composition:

[0100] Case 1: Please refer to Figure 7 and Figure 8 , Figure 7 This is a metallographic observation photo of a cross section of a tungsten wire provided in an embodiment of the present application. Figure 8 yes Figure 7 A local enlarged metallographic observation photograph at A. Take a tungsten wire with a diameter of 0.5 mm, whose outer shell has different metallographic structures and the thickness of the outer shell is 30 microns to 50 microns. The phase composition of this area is tested on the cross section of the tungsten wire.

[0101] Since the sample is pure tungsten wire, the three diffraction peaks of the oxides or carbides that may exist in the outer shell do not overlap with the diffraction peaks of tin foil, so tin foil can be used as a covering. Fig. 9 and Fig.10 , Fig. 9 This is a schematic diagram of the target area after the cover is covered. Fig.10 is a schematic diagram of etching the covering material at the area to be tested. Fig. 9 As shown, B is a raised mark formed at the area to be tested after covering with tin foil. The green circular area in the figure is tungsten wire, the green square area is tin foil, and the orange area is bakelite powder inlay material. Fig.10 As shown in FIG. 1 , a schematic diagram of etching the cover of the test area at B to expose the test area. Fig.11 , Fig.11 This is the XRD spectrum formed after the phase composition test of the tested area. A high-power rotating target X-ray diffractometer equipped with a micro-area accessory is used, the collimator tube diameter is 0.5mm, and the small angle area is slowly scanned. It can be seen that the main phase components are W2C and W, indicating that the outer shell layer of the tungsten wire is a carbide layer.

[0102] Case 2: Please refer to Fig.12 and Fig.13 , Fig.12 This is a metallographic observation photo of a high-temperature sintered silicon-molybdenum solder provided in an embodiment of the present application. Fig.13 This is a further enlarged metallographic observation photograph of the high-temperature sintered silicon-molybdenum solder. Fig.12 and Fig.13 The middle blue line area is the silicon-molybdenum solder sintered at 2000℃. The shape of the area is irregular and the phase composition of this area needs to be tested.

[0103] The diffraction ability of the matrix Mo is very strong, but it has little effect on the solder analysis, so a transparent melt can be used as a cover to reduce the intensity of the Mo diffraction peak. It should be noted that a metal sheet with a different diffraction peak from the silicon-molybdenum solder phase can also be used as a cover. Please refer to Fig.14 and Fig.15 , Fig.14 This is a schematic diagram of the target area after the cover is covered. Fig.15 is a schematic diagram of etching the covering material at the area to be tested. Fig.14 As shown, the area to be tested at C is marked with black ink. The green area in the figure is molybdenum, the black area is silicon-molybdenum solder, and the orange area is bakelite powder inlay material. Fig.15 As shown in FIG. 1 , a schematic diagram of etching the cover of the test area at C to expose the test area. Fig.16 , Fig.16 It is the XRD spectrum formed after the phase composition test of the test area. Using a common X-ray diffractometer, a slow scan of a small angle area shows that the main phase component of the solder is Mo3Si. It should be noted that there is Mo in the test area, and Mo has a strong diffraction ability, so Fig.16 There is Mo with a higher peak.

[0104] Case 3: Please refer to Fig.17 and Fig.18 , Fig.17 is a scanning electron microscope photograph of the coating cross section of a CVD coated blade provided in an embodiment of the present application, Fig.18 This is a scanning electron microscope photo of the coating cross section of the CVD coated blade that is further reduced. The thickness of the CVD coating D is only a few tens of microns, and the coating thickness is relatively small, while the substrate WC (adjacent to the CVD coating D cross section) where the coating is deposited has a strong diffraction ability, which is more than ten times that of the coating, and it is easy to cover the diffraction peak of the coating to be tested. Therefore, it is hoped that the influence of the substrate WC can be minimized, and an amorphous powder mixture can be added to the transparent melt as a covering. Please refer to Fig.19 and Fig. 20 , Fig.19 This is a schematic diagram of the target area after the cover is covered. Fig. 20 is a schematic diagram of etching the cover at the test area E. Since the test area is at the edge, no marking is required, such as Fig. 20 As shown in FIG. 1 , a schematic diagram of etching the covering of the test area to expose the test area. Fig.21 and Fig. 22 , Fig.21 This is the XRD comparison of the matrix WC before and after covering. Fig. 22 It is the XRD spectrum formed after the phase composition test of the tested area. Fig.21 It can be seen that after covering with transparent melt, the diffraction peak intensity of the matrix WC is about 1 / 5 of the original; after covering with a mixture of transparent melt and amorphous powder, the diffraction peak intensity of the matrix WC is basically 0. Using a high-power rotating target X-ray diffractometer and slow scanning of a small angle area, it can be seen that the main phase components of CVD coating D are Al2O3 and TiCN coating phases, and no matrix WC diffraction peaks are found.

[0105] It should be noted that in the accompanying drawings, the sizes of layers and regions may be exaggerated for clarity of illustration. It is also understood that when an element or layer is referred to as being "on" another element or layer, it may be directly on the other element, or there may be an intermediate layer. In addition, it is understood that when an element or layer is referred to as being "under" another element or layer, it may be directly under the other element, or there may be more than one intermediate layer or element. In addition, it is also understood that when a layer or element is referred to as being "between" two layers or two elements, it may be the only layer between the two layers or two elements, or there may also be more than one intermediate layer or element. Similar reference numerals throughout the text indicate similar elements.

[0106] In the present application, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance. The term "plurality" refers to two or more than two, unless otherwise clearly defined.

[0107] The above description is only an optional embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the protection scope of the present application.

Claims

1. A sample preparation method for XRD testing of micro-region phase composition, characterized in that: The method comprises: Selecting a test surface of the sample to be tested, and determining a test area on the test surface; Determine a covering, fix the covering on the surface to be tested and cover the area to be tested, the physical phase of the covering has no diffraction peak in the XRD spectrum, or the diffraction peak of the physical phase of the covering does not completely overlap with the diffraction peak of the physical phase of the area to be tested; The covering in the area to be tested is removed to expose the area to be tested.

2. The sample preparation method for XRD testing of micro-region phase composition according to claim 1, characterized in that: Determining the covering includes: If the diffraction peak of the physical phase in the area to be measured is known, the covering is a metal foil that does not completely overlap with the diffraction peak of the physical phase in the area to be measured or a transparent melt that has no diffraction peak after curing; If the diffraction peak of the physical phase in the region to be measured is unknown, the covering material is a transparent melt having no diffraction peak after curing.

3. The sample preparation method for XRD testing of micro-region phase composition according to claim 2, characterized in that: The melting point of the covering is below 450° C., the transparent melt is a paraffin-based melt, and the paraffin-based melt contains amorphous powder.

4. The sample preparation method for XRD testing of micro-region phase composition according to any one of claims 2-3, characterized in that: The method further comprises: A marker is arranged between the cover and the area to be tested, and the area to be tested is marked with the marker to indicate the position of the area to be tested.

5. The sample preparation method for XRD testing of micro-region phase composition according to claim 4, characterized in that: In the case where the covering material is transparent melt glue, the marking material is oily ink, and the marking material is distributed around the outer boundary of the area to be tested or covers the area to be tested; When the covering is a metal foil, the marker is an adhesive, and the marker is distributed around the outer boundary of the area to be tested or covers the area to be tested. After the metal foil covers the surface to be tested, the metal foil is pressed to make the metal foil at the edge of the area to be tested protrude.

6. The sample preparation method for XRD testing of micro-region phase composition according to any one of claims 2 to 5, characterized in that: The thickness of the metal foil is 20 micrometers to 40 micrometers, and the thickness of the transparent melt adhesive after curing is 200 micrometers to 500 micrometers.

7. A sample preparation device for XRD testing of micro-region phase composition, characterized in that: include: A mounting component, wherein the mounting component is used to fix the covering on the test surface of the sample to be tested and cover the test area on the test surface, and the physical phase of the covering has no diffraction peak in the XRD spectrum, or does not completely overlap with the diffraction peak of the physical phase in the test area; An etching component is used to etch the covering in the area to be tested to expose the area to be tested.

8. The sample preparation device for XRD testing of micro-region phase composition according to claim 7, characterized in that: The etching component comprises: a sample stage, a lifting bracket, a magnifying glass, an illuminator, a clamp and a heating device, wherein the sample stage is used to carry the sample to be tested, the lifting bracket is movably connected to the sample stage, the magnifying glass and the illuminator are both movably mounted on the lifting bracket; the heating device has a replaceable heating head, and the heating head is mounted on the clamp; The clamp is used to fix the heating head and can adjust the angle, and the heating device is used to etch the covering of the area to be tested through the heating head.

9. The sample preparation device for XRD testing of micro-region phase composition according to claim 8, characterized in that: The heating head is selected from at least one of a tungsten steel needle with a diameter of 0.1 μm-500 μm, an alloy tip with a diameter of 0.1 μm-500 μm, and an alloy flat head with a diameter of 1 mm-5 mm.

10. The sample preparation device for XRD testing of micro-region phase composition according to any one of claims 7 to 9, characterized in that: The device further comprises: a marker installation component, wherein the marker installation component is configured to carry a marker and mark the marker to the outer boundary of the area to be tested or cover the area to be tested.